Constructing Z-scheme SnO2/N-doped carbon quantum dots/ZnSn(OH)6 nanohybrids with high redox ability for NOx removal under VIS-NIR light. Issue 26 (17th June 2019) - Lu, Yanfeng; Huang, Yu; Cao, Jun-ji; Li, Haiwei; Ho, Wingkei; Lee, Shun Cheng
Abstract : Photocatalysts with a wide optical response range and high oxidation ability are essential for their application in air pollution control. Abstract : Photocatalysts with a wide optical response range and high oxidation ability are essential for their application in air pollution control. In this study, mesoporous SnO2 /NCDs/ZnSn(OH)6 (NCDs = N-doped carbon quantum dots) Z-scheme nanohybrids were synthesized for the first time using an in situ strategy. The ternary Z-scheme catalysts showed significantly enhanced visible and near-infrared light-driven photocatalytic activities for nitric oxide (NO) removal (37%), while the toxic nitrogen dioxide (NO2 ) intermediate was suppressed completely. The Z-schematic transfer mechanism was confirmed through characterizing the intrinsic properties of the as-prepared sample. The NCDs, as an electron transport bridge, improve both the broad-spectrum light-harvesting ability and the rapid separation of photoinduced electrons. Compared with the binary counterparts, the SnO2 /NCDs/ZnSn(OH)6 ternary nanohybrid can generate more reactive oxygen-containing radicals during the photocatalytic reaction, owing to its ability to supply sufficient free surface OH. This study provides insights into the heterogeneous photocatalytic Z-scheme reaction mechanism.